A new variance ratio test of random walk in emerging markets: A revisit - Al-Khazali, O. (Institutional Knowledge at Singapore Management University, 2007)
Using a nonparametric variance ratio (VR) test, we revisit the empirical validity of the random walk hypothesis in eight emerging markets in the Middle East and North Africa (MENA). After correcting for measurement biases caused by thin and infrequent trading prevalent in nascent and small stock markets, we cannot reject the random walk hypothesis for the MENA markets. We conclude that a nonparametric VR test is appropriate for emerging stock markets, and argue that our findings can reconcile previously contradictory results regarding the efficiency of MENA markets. [ABSTRACT FROM AUTHOR]